Creep constitutive model of siltstone subjected to wet-dry cycles. Issue 7 (October 2021) - Mo, Z K; Hou, D; Yao, C; Zhou, C B
Abstract: On the basis of the traditional Nishihara model, a nonlinear viscous pot with strain trigger is connected in series, the nonlinear relationship between creep parameters and the number of wet and dry cycles is established, and a nonlinear creep constitutive model of rock after wet and dry cycles is proposed. The proposed model is used to describe the whole process of the rheological test of siltstone after different drying and wetting cycles, and the parameters of the model are identified. Comparison between the creep data and the model results after different wet and dry cycles shows that the proposed nonlinear creep model can fully describe the creep process of each stage of the siltstone, and fully reflects the rheology of the initial creep, stable creep and nonlinear accelerated creep stages of the siltstone. Results have certain guiding significance for the analysis, evaluation and early warning of the long-term stability of reservoir bank slopes.